Henneguya shaharini sp. nov. (Protozoa: Myxozoa), a parasite of marble goby, Oxyeleotns marmoratus (Bleeker) - Shariff, M. (Wiley, 1982)
Henneguya shaharini sp. nov. is described from marble goby, Oxyeleotns marmoratus, collected in the State of Selangor, Malaysia. Cysts occurred in the gill filaments. The histopathological examination revealed intralamellar and inter‐lamellar forms of infection. A host tissue response against the parasite was seen in some fish.